The timed 25-foot walk in a large cohort of multiple sclerosis patients. (February 2022) - Kalinowski, Anissa; Cutter, Gary; Bozinov, Nina; Hinman, Jessica A; Hittle, Michael; Motl, Robert; Odden, Michelle; Nelson, Lorene M
Background: The timed 25-foot walk (T25FW) is a key clinical outcome measure in multiple sclerosis patient management and clinical research. Objectives: To evaluate T25FW performance and factors associated with its change in the Multiple Sclerosis Outcome Assessments Consortium (MSOAC) Placebo Database ( n  = 2465). Methods: We created confirmed disability progression (CDP) variables for T25FW and Expanded Disability Status Scale (EDSS) outcomes. We used intraclass correlation coefficients (ICCs) and Bland Altman plots to evaluate reliability. We evaluated T25FW changes and predictive validity using a mixed-effects model, survival analysis, and nested case–control analysis. Results: The mean baseline score for the T25FW in this study population was 9.2 seconds, median = 6.1 (standard deviation = 11.0, interquartile range (IQR) = 4.8, 9.0). The T25FW measure demonstrated excellent test–retest reliability (ICC = 0.98). Walk times increased with age, disability, disease type, and disease duration; relapses were not associated with an increase. Patients with T25FW progression had a faster time to EDSS-CDP compared to those without (hazards ratio (HR): 2.6; confidence interval (CI): 2.2, 3.1). Changes in the T25FW were more likely to precede changes in EDSS. Conclusion: This research confirms the association of the T25FW with disability and provides some evidence of predictive validity. Our findings support the continued use of the T25FW in clinical practice and clinical trials.